PENGARUH KEMISKINAN DAN PENDAPATAN TERHADAP PERCERAIAN PADA MASYARAKAT DI PROVINSI JAMBI - Ramadhani, Qori; Anderson, Irzal; Kuswanto, Kuswanto; Hajri, Priazki (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to determine the effect of poverty and income on divorce among people in Jambi Province. The divorce rate among people in Jambi Province for the 2018-2021 period has increased. In 2018 the divorce rate in Jambi Province was 4183, in 2019 there were 4979, in 2020 there were 7587, in 2021 there were 10,000 divorce rates. This research is a quantitative research using the Ex Post Facto research method conducted in 10 regencies/cities in Jambi Province in period 2018-2021. The research data is secondary data obtained from publication data by the Jambi Central Bureau of Statistics. The data was analyzed by Panel Data Regression Test through Eviews 12 software. The results showed that simultaneously poverty and income affect divorce in people in Jambi Province with a probability value of f-statistic, namely 0.007123 <0.05, also seen from the R-Square value, which is 0.0234, meaning that poverty and income contribute to influencing divorce by 23.4% and the rest influenced by other factors outside of this study. Poverty partially has no effect on divorce as evidenced by the probability value of the t-statistic, namely 0.0548 > 0.05. Income partially has a significant effect on divorce with a probability value of t-statistic 0.0411 <0.05.